2018
DOI: 10.1101/420646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive selection against microRNA target sites in human populations

Abstract: MicroRNA target sites are often conserved among related species. On the other hand, purifying selection against novel microRNA target sites can also exist. However, the relative impact of conservation versus selection against target sites is still unknown. We investigated these processes in human populations by focusing on polymorphic sites in which one allele is a target site and the other is not. Target allele frequencies were significantly lower than expected at these sites. The analysis of derived allele f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In microRNA target sites, some studies have shown that, as expected, functional target sites are often conserved in populations [19,20]. On the other hand, the creation of novel, potentially harmful, microRNA target sites, is selected against in populations [21,22]. In summary, the literature clearly shows evidence that nucleotide variation occurs at microRNA target sites.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In microRNA target sites, some studies have shown that, as expected, functional target sites are often conserved in populations [19,20]. On the other hand, the creation of novel, potentially harmful, microRNA target sites, is selected against in populations [21,22]. In summary, the literature clearly shows evidence that nucleotide variation occurs at microRNA target sites.…”
Section: Introductionmentioning
confidence: 73%
“…We found 11 target sites with such a degree of variation across populations (Table 1) for highly expressed microRNAs. In general, these target sites are lost in Out-of-Africa populations, suggesting that losses rather than the gains of target sites are more likely to happen during differentiation between populations (see discussion in [22]). HM13 rs6059873 0.0000 0.1844 0.8275 0.1571 0.0378 0.7298 a SNP names are dbSNP accession numbers.…”
Section: Resultsmentioning
confidence: 99%
“…To explore variation at target sites in pre-computed lists, the ‘Browse’ form allows to study microRNAs with different levels of expression, expression breath, evolutionary conservation and even sub-population structure. For instance, we recently reported that in human populations there is detectable selection against microRNA target sites (6). We can explore some specific cases with PopTargs.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that their targets can be predicted from their primary sequence has been exploited to study the potential impact of single-nucleotide polymorphisms at their target sites. Indeed, a number of studies have reported selective pressures at these target sites by investigating the variation in populations (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%